The biology of plant-insect interactions : a compendium for the plant biotechnologist - Emani, Chandrakanth (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
"Overviews of biochemical, genetic, and molecular perspectives of plant-insect interactions with added emphasis on bioinformatic, genomic, and transcriptome analysis are comprehensively treated in this book. It presents the agro-ecological and evolutionary aspects of plant-insect interactions with an exclusive focus on the climate change effect on the resetting of plant-insect interactions. A valued resource for biologists, students, policymakers, and the general public, the book includes theoretical aspects as a base toward real-world applications of holistic integrated pest management in agro-ecosystems."--Provided by publisher.
chapter 1 Plant Protease Inhibitors and their Interactions with Insect Gut Proteinases / S.M.D. Akbar -- r Mirzakamol S. Ayubov -- chapter 4 The Coevolution of the Plant-Insect Interaction Networks / Kevin Corneal -- chapter 5 Linking Primary and Secondary Metabolism A Mechanistic Hypothesis for how Elevated CO2 Modulates Defenses / Linus Gog -- chapter 6 Transgenic approaches to combatting insect pests in the field / Jennifer Campbell -- chapter 7 Metabolomics of plant resistance to insects / Mirka Macel -- chapter 8 RNAi and microRNA Technologies to Combat Plant Insect Pests / Vemanna S. Ramu -- chapter 9 Overview of the Biosafety and Risk Assessment Steps for Insect-resistant Biotech Crops / Venera Kamburova -- chapter 10 Towards a Holistic Integrated Pest Management Lessons Learned from Plant-Insect Mechanisms in the Field / Xiomara Sinisterra-Hunter.
"A science publishers book."
Keywords: Beneficial insects; Insect-plant relationships; Insects -- Effect of global warming on; Plants -- Disease and pest resistance; Plants -- Effect of global warming on; Plants -- Insect resistance